A pedagogical model to deconstruct vídeos in virtual learning environments - Moreira, J. António (2015)
In times of profound change, and given the breakneck speed at which information and communication technologies (ICTs) are developing, we often feel the need to (re)think the teaching-learning processes in an ever more plural school in which pedagogy has to be versatile and customised. The video is recognized by most teachers as a powerful communications medium which, in combination with other learning resources and instructional strategies, can perform a vital role in modern education. With the intention of renewing and innovating these processes, many teachers have sought to use videos. For pedagogical, technological or training reasons, however, this has not always been an easy task. The purpose of this paper is to reflect on these issues, presenting a pedagogical model to deconstruct videos in order to promote their efficient use in virtual learning environments.